OPTIMIZATION OF THE RECRUITMENT PROCESS AS A NECESSARY CONDITION FOR THE DEVELOPMENT OF THE ORGANIZATION - Ходирєва, О.О. (Управління змінами та інновації, 2022)
The work is devoted to the analysis of the main aspects of the personnel selection process and its direct impact on the development of the enterprise. The object of the research is the system of recruitment and selection by the method of conducting interviews. Analyze the state and methods of personnel selection, identify the main trends and problems in modern business conditions and provide recommendations for their solution to ensure sustainable development of enterprises and increase the level of economic potential of the enterprise. To solve this scientific problem used: structural method; comparative analysis of empirical data; abstract-logical generalization. The provisions and conclusions presented in the work are the result of the analysis of theoretical and practical material of applied researches of domestic and foreign authors. The essence and importance of the personnel selection process are substantiated and its influence on the development and effectiveness of the enterprise is revealed. The practical relevance of the research is determined by the possibility of qualitative change in the development of the enterprise through the use of more relevant tools for recruitment and ways to improve it.